143k views
2 votes
Express the equation in rectangular form
a) r = 2sin(2Θ)
b) r = 4cos(3Θ)

User Nasmorn
by
5.5k points

1 Answer

3 votes

Answer:

a. sqrt(x^2+y^2) * (x^2+y^2) = 4xy

b. (x^2+y^2)^2 = 4x{ (x^2 - 3 y^2}

Explanation:

a) r = 2sin(2Θ)

r* = 2 sin 2 theta

We know sin 2theta = 2 sin theta cos theta

r = 2 * 2 sin theta cos theta

sin theta = y/r and cos theta = x/r

r = 4 y/r * x/r

r = 4xy / r^2

Multiply each side by r^2

r^3 = 4xy

r * r^2 = 4xy

We know r = sqrt(x^2+y^2) and r^2 = (x^2+y^2)

sqrt(x^2+y^2) * (x^2+y^2) = 4xy

b) r = 4cos(3Θ)

we know that cos 3 theta = cos^3(theta) - 3 sin^2(theta) cos(theta)

r = 4 *cos^3(theta) - 3 sin^2(theta) cos(theta)

Factor out a cos theta

r = 4 *cos(theta){ cos^2 (theta) - 3 sin^2(theta) }

We know that sin theta = y/r and cos theta = x/r

r = 4 (x/r) { (x/r)^2 - 3 (y/r)^2}

r = 4 *(x/r) { (x^2/r^2 - 3 y^2/r^2}

Multiply by r

r^2 = 4x { (x^2/r^2 - 3 y^2/r^2}

Multiply by r^2

r^2 *r^2 = 4x { (x^2 - 3 y^2}

r^4 = 4x{ (x^2 - 3 y^2}

We know r^2 = (x^2+y^2)

(x^2+y^2)^2 = 4x{ (x^2 - 3 y^2}

User Unlut
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.